STILISTIKA PUISI KARYA MAHASISWA ASING DI IAIN TULUNGAGUNG - Maulida, Siti Zumrotul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This qualitative research aimed to describe the poetries of foreign students at IAIN Tulungagung. Most of the foreign students who study at IAIN Tulungagung are from Southern Thailand. Writing poetry is one of the language competence in the C2 level of BIPA (Bahasa Indonesia untuk Penutur Asing) curriculum. Seven   foreign students who study at the 6th semester of Indonesian Education Department also took part in writing poetry class and the elective courses of BIPA. From the results of lecturing, students had poetry that was important to be studied because it can be used as an evaluation of the success of mastering language skills and language. In order to fulfill this goal, the poetry was examined stylistically.  This Thai students’ poetry stylistic study combined the linguistic studies with a study of stylistic meaning. Linguistically, the results of  this study indicated that the writing poetry mastery of foreign students at IAIN Tulungagung through objective factor was still very simple. As for the stylistic meaning in the reader's response (affective factor),  Dominantly the poetries of foreign students at IAIN Tulungagung are humanistic problems. Hopefully, the results of this research can contribute in internationalizing of Bahasa Indonesia.